1996
DOI: 10.1111/j.1432-1033.1996.0655h.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Glu380 and Leu383 of Soybean β‐Amylase

Abstract: Soybean P-amylase, comprising a @/a),-barrel core with a mobile loop, similar to that of triose phosphate isomerase, was mutated by site-directed mutagenesis at residues Glu380 and Leu383. X-ray crystallographic findings suggest that Glu380 is the counterpart of the catalytic site (Glu186) and that Leu383, located near the active-site cavity, forms an inclusion complex with cyclomaltohexaose. Separate substitutions of Glu380 by Gln and Asp completely eliminated the activity without inducing any significant cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The structural analysis of the soybean maltose-␤-amylase complex indicated that Glu 186 and Glu 380 play important roles in the enzymatic reaction as general acid and base catalysts, respectively (16). This finding is supported by the results of site-directed mutagenesis (17,18) and affinity labeling (19). In addition, the structures of ␣-CD⅐␤-amylase and maltose⅐␤-amylase complexes revealed that a flexible loop plays a key role in the reaction.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The structural analysis of the soybean maltose-␤-amylase complex indicated that Glu 186 and Glu 380 play important roles in the enzymatic reaction as general acid and base catalysts, respectively (16). This finding is supported by the results of site-directed mutagenesis (17,18) and affinity labeling (19). In addition, the structures of ␣-CD⅐␤-amylase and maltose⅐␤-amylase complexes revealed that a flexible loop plays a key role in the reaction.…”
mentioning
confidence: 80%
“…Leu 383 , which forms an inclusion complex, is one of the residues that contribute to the slipping mechanism (12). Totsuka et al (18) suggested by site-directed mutagenesis that Leu 383 may work to bind polymeric substrate as a winder (18). Probably, Leu 383 plays an important role in the single chain attack mechanism as well as in the binding of polymeric substrate, because the residue seems to block the cleaved substrate from release into the solvent (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The structural analysis of the soybean ␤-amylase (SBA) 1 -maltose complex indicated that Glu 186 and Glu 380 play important roles in the enzymatic reaction as a general acid and a base catalyst, respectively (16). This finding is supported by the results of site-directed mutagenesis (22) and affinity labeling (23). In the case of B. cereus ␤-amylase (BCB), Glu 172 and Glu 367 act as the general acid and base catalyst, respectively, corresponding to Glu 186 and Glu 380 in soybean ␤-amylase (20,21).…”
mentioning
confidence: 84%
“…The three‐dimensional model of the C. sepium β‐amylase strongly resembles that of the soybean [33,39] and sweet potato [38]β‐amylases and shares the typical (α/β) 8 barrel core which is common to all other β‐amylases of different origins [44]. According to both structural [33,39] and functional data [45–47], four amino‐acid residues (Asp101, Glu186, Glu345 and Glu380) located in a cleft occurring between the (α/β) 8 barrel core and the smaller globular region play a key role in the catalytic activity of the soybean β‐amylase. These four residues are conserved in all other plant β‐amylases including the C. sepium β‐amylase.…”
Section: Discussionmentioning
confidence: 99%
“…origins [44]. According to both structural [33,39] and functional data [45][46][47], four amino-acid residues (Asp101, Glu186, Glu345 and Glu380) located in a cleft occurring between the (a/b) 8 barrel core and the smaller globular region play a key role in the catalytic activity of the soybean b-amylase. These four residues are conserved in all other plant b-amylases including the C. sepium b-amylase.…”
Section: Discussionmentioning
confidence: 99%